PENGARUH KUALITAS PELAYANAN, HARGA DAN PROMOSI TERHADAP KEPUASAN KONSUMEN PADA TOKO DESTAR ASLI BALI DI TABANAN - I Komang Gede Sugita Prameswara; Ni Made Hartini; Laras Oktaviani (Universitas Triatma Mulya, 2023)
This research is motivated by the phenomenon of consumer satisfaction (Y) at the Destar Asli Bali Store. This study aims to analyze and prove the effect of service quality (X1), price (X2), and promotion (X3) on consumer satisfaction (Y) at Destar Asli Bali Store. This study uses quantitative methods. The sample technique used is purposive sampling technique. The number of respondents used is 100 consumers. Multiple linear regression analysis using SPSS software version 24. The regression equation obtained: Y = 6.392 + 0.232X1 + 0.219X2 + 0.121X3. The results of this study indicate that: First, service quality has a positive effect on customer satisfaction (Y) at the Destar Asli Bali Store. Second, the price has a positive effect on consumer satisfaction (Y) at the Destar Asli Bali Shop. Third, promotion has a positive effect on consumer satisfaction (Y) at the fourth Destar Asli Bali Store, the data used proves service quality (X1), price (X2), and promotion (X3), which together have a positive and significant effect on satisfaction. consumer (Y) at the Destar Asli Bali Store. Fifth, the magnitude of the influence contributed by the quality of service, price, and promotion on consumer satisfaction (Y) at Destar Asli Bali Store is 18.4%.